1998
DOI: 10.1038/sj.sc.3100662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal nimodipine on spinal cord blood flow and evoked potentials in the normal or injured cord

Abstract: A method was developed for administering intrathecal pharmacotherapy in a rat model of spinal cord injury. The eects of intrathecal administration of nimodipine on spinal cord blood¯ow (SCBF) and evoked potentials (EPs) were measured in the normal and injured spinal cord. It had previously been shown that systemic nimodipine caused severe hypotension after spinal cord injury. After baseline SCBF and EPs, 15 uninjured rats were blindly allocated to one of three groups: one placebo group (n=5); and two groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…There have been many studies on the effects of intrathecal administration of various drugs on SCBF. 10,11 Nimodipine has been investigated as a treatment for SCI. It had previously been shown that systemic nimodipine causes severe hypotension after SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies on the effects of intrathecal administration of various drugs on SCBF. 10,11 Nimodipine has been investigated as a treatment for SCI. It had previously been shown that systemic nimodipine causes severe hypotension after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thus, intrathecal administration of nimodipine did not prevent the hypotension encountered with systemic administration and exerted no beneficial effect on SCBF after acute SCI. 11 Papaverine has been used to protect the spinal cord from ischemic damage while operating on the descending or thoracoabdominal aorta. It was administered Figure 1 Spinal cord blood flow (SCBF) over time as assessed by the laser flow blood perfusion monitor.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in rats using clip compression injury have demonstrated bene®cial eects on evoked potentials after drug treatments. 7,35,43 To check the lesion severity and evoked potential responses, we performed a preliminary study using the same aneurysm clip (50 g) for 1 min compression injury, and we were not able to analyse the amplitudes because of the large number of absent responses; thus the compression time was chosen to be 30 s. In our study, decline in the amplitudes if SSEPs occurred after clip compression signi®cantly improved in highdose magnesium treated group. However, the decreased amplitudes did not recover in saline treated and low-dose magnesium treated groups.…”
Section: Discussionmentioning
confidence: 98%
“…31 ± 33 Calcium antagonists have been shown to increase blood¯ow in the brain and spinal cord, and decrease cellular toxicity; thus, they have been extensively studied in spinal cord trauma. 1,7,33,35 Neuroprotective eects of magnesium has been shown in experimental models of permanent focal cerebral ischemia, transient global ischemia, spinal cord ischemia, traumatic brain injury, topically induced quinolinate hippocampal neurodegeneration, perinatal postasphyxial brain damage, and delayed cerebral vasospasm after subarachnoidal haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that calcium channel blockers have positive effects on microcirculation and spinal perfusion after SCI. Calcium channel blockers have been shown to increase blood flow in the spinal cord after trauma in many studies [5, 6]. They selectively inhibit peripheral vasodilatation by acting on CNS veins and prevent ischemic deficits.…”
Section: Discussionmentioning
confidence: 99%